COVID-19 Vaccination to realize Green Zones in Bali - Ida Ayu Agung Adnyawati (Bali Tourism Journal, 2021)
Bali Governor I Wayan Koster revealed that The Bali Provincial Government had developed COVID-19 Free Green Zone as a COVID-19 Free area for tourism. Three areas have been proposed to be a COVID-19 free green zone. There were Ubud in Gianyar Regency, the Nusa Dua Indonesia Tourism Development Corporation (ITDC) Region in Badung Regency and Sanur in Denpasar City. The plan was regulated on Circular letter Number 6 of 2021 concerning the Extension of Village-Based micro-scale social restriction. It was expected that all attractions within the zone would be declared COVID-19 accessible areas, which means domestic and foreign tourists can visit. Mass COVID-19 vaccination would be carried out for people within the zone to ensure the areas' safety. The head of the Bali Provincial Health Office, Ketut Suarjaya, confirmed that the vaccination started on 16 March 2021, after the celebration of Nyepi. Each district government performed each vaccination stage until June. The CoronaVac vaccine, which expired on 25 March 2021, had been fully used for first and second doses targeting Bali's health workers. Meanwhile, the latest vaccines used for public servants, the elderly and other targets were multi-dose vaccines of AstraZeneca. The Bali Provincial Government, from mid to the end of March 2021, received 200,000 doses or vials of the AstraZeneca vaccine. The Bali Provincial Health Office head said there had been no Post-Immunization Adverse Events (AEFI) reports. Therefore the vaccination in Bali would continue.